1996
DOI: 10.1046/j.1365-2133.1996.d01-738.x
|View full text |Cite
|
Sign up to set email alerts
|

Human epidermal Langerhans cells express the ICAM-3 molecule. Immunohistochemical and immunoelectron microscopical demonstration

Abstract: Three ligands have been described for the leucocyte integrin LFA-1, namely intercellular adhesion molecule (ICAM)-1, ICAM-2, and ICAM-3. ICAMs show differences in tissue distribution and inducibility. The recently described ICAM-3 is highly expressed on resting lymphocytes, monocytes and neutrophils. Here, we demonstrate that the whole human epidermal Langerhans cell (LC) population expresses this molecule. Immunohistochemical staining of skin sections with an anti-ICAM-3 monoclonal antibody displayed reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…This comparative analysis revealed that LC, residing in the epidermis under steady-state conditions, exhibit a nonstimulatory phenotype. As illustrated by Figure 2, LC display a nonmigratory profile, expressing molecules involved in cell adhesion such as Ecadherin, ICAM-3, and epidermal surface antigen or involved in DC retention such as junctional adhesion molecules and CD47 but lacking expression of molecules involved in DC migration such as CCR7 (Table 3), as also described by others [10,[33][34][35][36]. Indeed, ligation of CD47, also known as integrinassociated protein, has been demonstrated to regulate LC maturation and migration, resulting in the suppression of LC function, inhibition of T cell priming, and the subsequent inhibition of the establishment of an immune response [37].…”
Section: Lc Display a Nonimmunogenic Nonmigratory Phenotype Under Stmentioning
confidence: 77%
“…This comparative analysis revealed that LC, residing in the epidermis under steady-state conditions, exhibit a nonstimulatory phenotype. As illustrated by Figure 2, LC display a nonmigratory profile, expressing molecules involved in cell adhesion such as Ecadherin, ICAM-3, and epidermal surface antigen or involved in DC retention such as junctional adhesion molecules and CD47 but lacking expression of molecules involved in DC migration such as CCR7 (Table 3), as also described by others [10,[33][34][35][36]. Indeed, ligation of CD47, also known as integrinassociated protein, has been demonstrated to regulate LC maturation and migration, resulting in the suppression of LC function, inhibition of T cell priming, and the subsequent inhibition of the establishment of an immune response [37].…”
Section: Lc Display a Nonimmunogenic Nonmigratory Phenotype Under Stmentioning
confidence: 77%
“…MHC class I was constitutively expressed, particularly on the basal cells of infundibula, and was apparently unaffected by exogenous cytokines (Table I). ICAM-3 was not constitutively expressed by keratinocytes or in response to exogenous cytokines (Table I); however, individual cells were seen to stain with ICAM-3 that we attribute to the presence of Langerhans cells (Manara et al, 1996). PMA for 24 h stimulated both ICAM-1 and HLA-DR expression in all infundibula (Table I); however, by 3 d, PMA treated infundibula expressed neither ICAM-1 nor HLA-DR (Table I).…”
Section: Infundibula Retain Their Pattern Of Differentiation Over 7 D Of Maintenancementioning
confidence: 77%
“…These changes are thought to facilitate migration of Langerhans cells from skin to DLN and are indicative of activated Langerhans cells (Larsen et al, 1990;Kondo and Sauder, 1995) and are thought to involve downregulation of E-cadherin (Borkowski et al, 1994;Jakob and Udey, 1998). Following activation, Langerhans cells express a number of cell surface markers including B7, ICAM-1, and ICAM-3 and increase their expression of major histocompatibility complex (MHC) class II antigens (Shimada et al, 1987;Aiba and Katz, 1990;Tang and Udey, 1991;Manara et al, 1996;Laihira and Jansen, 1997). As Langerhans cells play a crucial part in immunosurveillance there has been considerable interest in agents that modify Langerhans cell function (Simon et al, 1992;Bacci et al, 1996;Ozawa et al, 1996;Qu et al, 1997).…”
mentioning
confidence: 99%